Techniques for Teaching Speaking Skill in Widya Gama Mahakam University - Arbain Arbain; Dedi Rahman Nur (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
Speaking as one of the four skills in English is seen as the most crucial skill to be mastered by English learners. For most people the successes in learning a language can be seen from how far the student can speak and communicate in the language learn. But in fact, speaking is often neglected in the classroom. The objective of this research is to investigate techniques in teaching speaking skill in second semester of primary school department of Widya Gama Mahakam University. This study employs the qualitative design by which the researcher intends to discover and understand techniques of teaching speaking used by the lecture in its natural setting. The subject of this research was second semester students of primary school department. This study reveals four techniques employed by the lecturer in teaching speaking skill, i.e. show-and-tell, presentation, drama making, and question and answer. Show-and-tell and presentation technique are two types of performance talk which were used more often by the lecturer than the two other techniques (i.e. drama making and question and answer).